Targeted Therapy in Ewing Sarcoma. (28th May 2012) - Lissat, A.; Chao, M. M.; Kontny, U.
Abstract : Despite marked improvement in the prognosis of patients with nonmetastatic Ewing sarcoma (ES), the outcome for patients with recurrent or metastatic disease remains poor. Insight into key biologic processes in ES could provide new therapeutic targets. The particular biologic feature of ES, the fusion of the EWS gene with a member of the ETS family of genes, is present in >95% of cases. The EWS-ETS chimeric protein leads to aberrant transcription that promotes tumor initiation and propagation via prosurvival and antiapoptotic pathways. Recent research has identified cooperating mutations important for ES tumorigenesis. This paper provides a summary of the latest research in ES and discusses potential novel targets for therapy.